Pasar Persaingan Sempurna: Analisis Karakteristik, Efisiensi, dan Relevansi di Era Modern: Analisis karakteristik , efisiensi,dan relevansi di era modern - Munawaroh, Habibah Munawaroh (Maliki Interdisciplinary Journal, 2025)
an perfect show in financial hypothesis characterized by a expansive number of buyers and dealers, homogeneous items, symmetric data, and the nonappearance of obstructions to section and exit. This show gives an critical hypothetical establishment for understanding showcase instruments and proficient asset assignment. The investigation covers the most characteristics of flawlessly competitive markets, the conditions that must be met, as well as the coming about allocative and profitable proficiency. Moreover, this article too investigates the relevance of idealize competition within the advanced period, considering energetic changes in innovation, globalization, and controls that influence real advertise structures. A perfectly competitive market is an ideal model that provides an important theoretical basis for understanding market mechanisms and efficient resource allocation. This model has many buyers and sellers in the market.